Disorder as “Pseudo-Idea” - Angelides, Steven (Atlantis, 2012)
This essay deconstructs the order/disorder binary. Drawing on the work of Henri Bergson, it replaces the idea of disorder with the concept of two positive orders. The essay concludes with a philosophical example of how we might reconceive the biomedical opposition of normality/pathology without relying on the idea of disorder.